Pro HTML5 Performance - Bryant, Jay; Jones, Mike (Apress : Imprint: Apress, 2012)
Pro HTML5 Performance provides a practical guide to building extremely fast, light-weight and scalable websites using fully standards compliant techniques and best practices. It strikes a balance between imparting best-practice information for when you're building ground up and instantly applicable techniques to help you solve issues with your existing projects. In addition to a wealth of tips, tricks and secrets you'll find advice and code samples that elegantly layout the problems your facing and the best ways of solving them. By reading Pro HTML5 Performance you'll squeeze every last ounch of performance from your code, giving your applications unrivalled speed and cost-efficiency.